Interpreted modelling for safety and emissions at roundabouts and traffic signals in corridors - Fernandes, Paulo Jorge Teixeira (2020)
Scientific research has demonstrated that the operational, environmental and safety performance for pedestrians depend on the geometric and traffic stream characteristics of the roundabout. However, the implementation of roundabouts may result in a trade-off among capacity, environmental, and safety variables. Also, little is known about the potential impacts for traffic from the use of functionally interdependent roundabouts in series along corridors. Thus, this doctoral thesis stresses the importance of understanding in how roundabout corridors affect traffic performance, vehicular emissions and safety for vulnerable users as pedestrians. The development of a methodology capable of integrating corridor’s geometric and operational elements is a contribution of this work. The main objectives of the thesis are as follows: 1) to analyze the effect of corridor’s design features in the acceleration patterns and emissions; 2) to understand the differences in the spatial distribution of emissions between roundabouts in isolation and along corridors; 3) to compare corridors with different forms of intersections such as conventional roundabouts, turbo-roundabouts, traffic lights and stop-controlled intersections; and 4) to design corridor-specific characteristics to optimize vehicle delay, and global (carbon dioxide – CO2) and local (carbon monoxide – CO, nitrogen oxides – NOX and hydrocarbons – HC) pollutant emissions. Vehicle dynamics along with traffic and pedestrian flow data were collected from 12 corridors with conventional roundabouts located in Portugal, Spain and in the United States, 3 turbo-roundabout corridors in the Netherlands, and 1 mixed roundabout/traffic-lights/stop-controlled corridor in Portugal. Data for approximately 2,000 km of road coverage over the course of 50 h have been collected. Subsequently, a microscopic platform of traffic (VISSIM), emissions (Vehicle Specific Power – VSP) and safety (Surrogate Safety Assessment Model – SSAM) was introduced to faithful reproduce site-specific operations and to examine different alternative scenarios. The main research findings showed that the spacing between intersections influenced vehicles acceleration-deceleration patterns and emissions. In contrast, the deflection angle at the entrances (element that impacts emissions on isolated roundabouts) impacted slightly on the spatial distribution of emissions. It was also found that the optimal crosswalk locations along mid-block sections in roundabout corridor was generally controlled by spacing, especially in the case of short spacing between intersections (< 200 m). The implementation of turbo-roundabout in series along corridors increased emissions compared to conventional two-lane roundabout corridors (1-5%, depending on the pollutant). By changing the location of a roundabout or turbo-roundabout to increase spacing in relation to upstream/downstream intersection resulted in an improvement of corridor emissions. Under conditions of high through traffic and unbalanced traffic flows between main roads and minor roads, vehicles along roundabout corridors produced fewer emissions (~5%) than did vehicles along signalized corridors, but they emitted more gases (~12%) compared to a corridor with stop-controlled intersections. This research contributed to the current state-of-art by proving a full comprehension about the operational and geometric benefits and limitations of roundabout corridors. It also established correlations between geometric variable of corridors (spacing), crosswalk locations or traffic streams, and delay, and CO2, CO, NOX or HC variables. With this research, it has been demonstrated that the implementation of a given intersection form within a corridor focused on minimizing CO2 may not be translated to other variables such as CO or NOX. Therefore, the develop methodology is a decision supporting tool capable of assessing and selecting suitable traffic controls according the site-specific needs.